Role Of Computational Simulations In The Design Of Piston Rings - Novotný Pavel; Raffai Peter; Dlugoš Jozef; Maršálek Ondřej; Knotek Jiří (Journal of Middle European Construction and Design of Cars, 2015)
The paper presents computational approaches using modern strategies for a dynamic piston ring solution as a fluid structural problem. Computational model outputs can be used to understand design parameter influences on defined results of a primarily integral character. Piston ring dynamics incorporates mixed lubrication conditions, the influence of surface roughness on oil film lubrication, the influence of ring movement on gas dynamics, oil film formulation on a cylinder liner and other significant influences. The solution results are presented for several parameters of SI engine piston rings.